Effect of Biochar on Micronutrient Availability and Uptake Into Leafy Greens in Two Urban Tropical Soils With Contrasting Soil pH - Rodríguez-Vila, Alfonso; Atuah, Laura; Abubakari, Abdul Halim; Atorqui, Dickson Worlanyo; Abdul-Karim, Alhassan; Coole, Sean; Hammond, John; Robinson, Steve; Sizmur, Tom (Frontiers in Sustainable Food Systems, 2022)
Biochars have been proposed as a novel biotechnology to increase crop yields in acidic soils due to a liming effect. However, the application of biochar to soils with a neutral soil pH is less likely to improve yield. A rise in pH typically increases the availability of macronutrients (e.g. PO43-, NO3-) but may immobilize some micronutrients due to adsorption. Therefore, biochar application may reduce the uptake of important micronutrients (e.g. Cu, Fe, and Zn) into the edible portions of food crops. Before recommending indiscriminate biochar application to tropical soils, an understanding of the potentially negative impacts of biochar application to contrasting soil types should be fully appreciated to prevent unintended consequences. Our aim was to determine the impact of biochar amendment to an acidic soil and a neutral soil on micronutrient availability and uptake into leafy greens. We produced biochars from 3 different organic feedstock materials (corn cobs, rice husk and teak sawdust) and applied these in pot experiments to an acidic tropical soil (pH 4.5) and a neutral tropical soil (pH 6.9) collected from urban farms in Tamale and Kumasi, respectively, in Ghana. We grew leafy greens (Amaranthus, Corchorus, and Lettuce) and measured their growth and the uptake of Cu, Fe, and Zn , alongside supporting measurements of soil pH and micronutrient availability in the soil. The corn cobs biochar increased soil pH and plant growth in the acidic soil from Tamale. In the neutral soil from Kumasi we found that, while corn cob biochar increased soil pH, rice husk biochar decreased soil pH. Furthermore, corn cob biochar considerably reduced plant growth in the neutral soil. The concentration of micronutrients in the edible portions of leafy greens was not greatly affected by biochar application, but the total uptake of micronutrients into leaves was generally increased by biochar application in the acidic soil and the corn cob biochar generally decreased uptake of micronutrients from neutral soil. We highlight the need for site-specific information on biochar feedstock and soil pH prior to biochar application to tropical urban soils so that the benefits can be optimized and unintended consequences prevented.